Preparation and Characterization of Succinyl‐Chitosan Nanoparticles for Drug Delivery. Issue 1 (25th August 2015) - Monsalve, Yuliana; Sierra, Ligia; López, Betty L.; Chirachanchai, Sawabu; Hoven, Voravee; Sojamsang, Warayuth
Summary Succinyl‐Chitosan (SCS), a water soluble CS derivative, exhibits biocompatibility, low toxicity and long‐term retention in the body. SCS offers unique characteristics as polymer for obtaining drug delivery nanosystems, due to its many reactive amino, hydroxyl, and carboxylic acid pendant groups. Chemical modifications of SCS with antibodies and other active species are easily achieved through bonding with these groups, allowing targeting and detection. In this work, SCS was obtained by amidation of primary amine groups of CS with succinic anhydride. The succinylation degree, determined by 1H‐NMR, was 28%. Evaluation by zeta potential measurements of SCS showed a pH‐dependent charge profile, which can be conveniently exploited to prepare pH‐sensitive nanoparticles. Colloidal stable SCS/CS and SCS nanoparticles, useful in drug delivery, were prepared by ionic crosslinking from mixtures of CS and SCS in different weight percentages. Nanoparticles with sizes between 140–250 nm (after purification process) are obtained, which through further surface functionalization are suitable for application in drug delivery. The colloidal stability of the particles in water was studied by particle size measurements during 30 days and aggregation or formation of larger particles was not observed.